2016
DOI: 10.1186/s13071-016-1507-4
|View full text |Cite
|
Sign up to set email alerts
|

The sandfly Lutzomyia longipalpis LL5 embryonic cell line has active Toll and Imd pathways and shows immune responses to bacteria, yeast and Leishmania

Abstract: BackgroundLutzomyia longipalpis is the main vector of visceral leishmaniasis in Latin America. Sandfly immune responses are poorly understood. In previous work we showed that these vector insects respond to bacterial infections by modulating a defensin gene expression and activate the Imd pathway in response to Leishmania infection. Aspects of innate immune pathways in insects (including mosquito vectors of human diseases) have been revealed by studying insect cell lines, and we have previously demonstrated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 39 publications
1
39
0
Order By: Relevance
“…Roles for insect immunity in controlling their transmission of infectious pathogens have been reported previously, including transmission of dengue virus by Aedes aegypti mosquitos (5)(6)(7), of African trypanosomes by the tsetse fly Glossina morsitans (8), and of malaria parasites by Anopheles gambiae (9,10). Concerning sand flies, a previous study showed that both the Toll and IMD pathways are activated by yeast, bacteria, and Leishmania in cultured Lutzomyia longipalpis sand fly cells (11). A defensin AMP was produced in Phlebotomus duboscqi flies after challenge by injected bacteria or feeding with bacteria or L. major and also presented an antiparasitic action in vitro (12).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Roles for insect immunity in controlling their transmission of infectious pathogens have been reported previously, including transmission of dengue virus by Aedes aegypti mosquitos (5)(6)(7), of African trypanosomes by the tsetse fly Glossina morsitans (8), and of malaria parasites by Anopheles gambiae (9,10). Concerning sand flies, a previous study showed that both the Toll and IMD pathways are activated by yeast, bacteria, and Leishmania in cultured Lutzomyia longipalpis sand fly cells (11). A defensin AMP was produced in Phlebotomus duboscqi flies after challenge by injected bacteria or feeding with bacteria or L. major and also presented an antiparasitic action in vitro (12).…”
mentioning
confidence: 74%
“…Finally, while our CRISPR strategy focused only the IMD pathway, other pathways are of crucial importance in the insect immune response (3,4). A role for the Toll pathway seems especially likely in the sand fly response to Leishmania because, as with the IMD pathway, its activation was observed in vitro when cultured sand fly cells were exposed to bacteria or Leishmania (11), and upregulation of a gene encoding a defensin AMP, whose expression in Drosophila depends on Toll (3), was observed in flies infected with L. major (12,13).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of L. longipalpis , previous studies utilizing cell lines focused on the interaction of these cells with Leishmania (Rey et al , 2000 ; Cortes et al , 2011 ). Our group has investigated the response of LL5 cells to various organisms including viruses (Pitaluga et al , 2008 ) as well as yeast, Leishmania and bacteria (Tinoco-Nunes et al , 2016 ). LL5 challenges with the Gram− Staphylococcus aureus and the Gram+ Escherichia coli and S. marcescens activated the Toll and IMD pathways, with S. aureus and S. marcescens triggering an early response (Tinoco-Nunes et al , 2016 ).…”
Section: Sand Flies and Bacteria: Interdependence And Immune Responsementioning
confidence: 99%
“…Both pathways have been shown to play a role in the response to trypanosomatids 13,[34][35][36][37][38] . Furthermore, we also investigated members of the Dual-oxidase (DUOX) and JAK-STAT pathways, both of which were implicated in D. melanogaster-H. muscarum interaction 13 .…”
Section: Differential Expression Associated With Trypanosomatid Presementioning
confidence: 99%